Some Bioactivities of Limonium meyeri Extracts and their Separated Compounds - Masum Sami; Esen Sezen Karaoğlan; Hayrunisa Hancı; Cavit Kazaz (BioResources)
The antimicrobial and tyrosinase enzyme inhibition activities of various extracts and isolated compounds of Limonium meyeri were investigated. Apigenin-7-O-β-glucuronide and myricetin 3-O-α-rhamnoside were isolated from the ethyl acetate fraction using chromatographic methods. Methanol extract showed 62.0% and ethyl acetate extract showed 57.6% tyrosinase enzyme inhibition activities at 400 µg/mL concentration. Myricetin 3-O-α-rhamnoside (IC50 = 27.7 ± 0.6 µg/mL) showed higher tyrosinase enzyme inhibitory effect than apigenin-7-O-β-glucuronide (IC50 = 43.0 ± 0.9 µg/mL). n-Hexane extract was found to be effective against Enterococcus faecalis (MIC = 1 µg/mL), while methanol extract was effective against Pseudomonas aeruginosa (MIC = 16 µg/mL). Myricetin 3-O-α-rhamnoside showed antimicrobial effect against Enterococcus faecalis (MIC = 128 µg/mL). Thus, Limonium meyeri and its compounds may provide valuable insights for future studies as antityrosinase and antibacterial agents.